1999
DOI: 10.1103/physrevd.60.092004
|View full text |Cite
|
Sign up to set email alerts
|

Studies of nonlinear QED in collisions of 46.6 GeV electrons with intense laser pulses

Abstract: We r e p o r t on measurements of quantum electrodynamic processes in an intense electromagnetic wave, where nonlinear e ects (both multiphoton and vacuum polarization) are prominent. Nonlinear Compton scattering and electronpositron pair production have been observed in collisions of 46.6 GeV and 49.1 GeV electrons of the Final Focus Test Beam at SLAC with terawatt pulses of 1053 nm and 527 nm wavelengths from a Nd:glass laser. Peak laser intensities of 0:5 10 18 W/cm 2 have been achieved, corresponding to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
314
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(343 citation statements)
references
References 57 publications
12
314
0
2
Order By: Relevance
“…The theory of this nonlinear Compton effect (229) is given in Section 4.10. The same process (229) has been expressed by Bamber et al [211] in a semi-classical framework. The second is the nonlinear BreitWheeler process…”
Section: Nonlinear Compton Scattering and Breit-wheeler Processmentioning
confidence: 73%
“…The theory of this nonlinear Compton effect (229) is given in Section 4.10. The same process (229) has been expressed by Bamber et al [211] in a semi-classical framework. The second is the nonlinear BreitWheeler process…”
Section: Nonlinear Compton Scattering and Breit-wheeler Processmentioning
confidence: 73%
“…Invariably, the Eddington conjecture was formulated before the advent of modern particle accelerators and lasers where particle creation processes may be studied; e.g., a now rather famous experiment at the Stanford Linear Accelerator Center (SLAC) described in Refs. [52,53] has shown that electrons may be created in strong laser fields, after the injection of a highly energetic γ ray emitted by Compton backscattering from an energetic oncoming electron.…”
Section: Eddington Conjecturementioning
confidence: 99%
“…, χ e = 0.3, and χ γ =0.15) [108,109]. The modern day laser systems can produce 100 a  , and GeV-level electron beams, which not only will boost the classical and quantum nonlinearities, but also significantly reduce the characteristic scale of the process, resulting in a cascade-type multistage process in the interaction of an electron beam with an intense laser pulse.…”
Section: Prospects Of High Field Science Experimentsmentioning
confidence: 99%
“…In Table 1 we summarize the parameters of the proposed experiment on the ultrarelativistic electron beam interaction with an intense PW-class laser pulse (see [107,109]). We note that the PW class laser (upgraded J-KAREN) has a potential for accelerating electrons up to 10 GeV energy.…”
Section: Prospects Of High Field Science Experimentsmentioning
confidence: 99%